Amiodarone reduces depolarization-evoked glutamate release from hippocampual synaptosomes - Chia Yu Chang; Chi Feng Hung; Shu Kuei Huang; Jinn Rung Kuo; Su Jane Wang (Elsevier, 2017)
Decreased brain glutamate level has emerged as a new therapeutic approach for epilepsy. This study investigated the effect and mechanism of amiodarone, an anti-arrhythmic drug with antiepileptic activity, on glutamate release in the rat hippocampus. In a synaptosomal preparation, amiodarone reduced 4-aminopyridine-evoked Ca2+-dependent glutamate release and cytosolic Ca2+ concentration elevation. Amiodarone did not affect the 4-aminopyridine-evoked depolarization of the synaptosomal membrane potential or the Na+ channel activator veratridine-evoked glutamate release, indicating that the amiodarone-mediated inhibition of glutamate release is not caused by a decrease in synaptosomal excitability. The inhibitory effect of amiodarone on 4-aminopyridine-evoked glutamate release was markedly decreased in synaptosomes pretreated with the Cav2.2 (N-type) and Cav2.1 (P/Q-type) channel blocker ω-conotoxin MVIIC, the calmodulin antagonists W7 and calmidazolium, or the protein kinase A inhibitors H89 and KT5720. However, the intracellular Ca2+-release inhibitors dantrolene and CGP37157 had no effect on the amiodarone-mediated inhibition of glutamate release. Furthermore, amiodarone reduced the frequency of miniature excitatory postsynaptic currents without affecting their amplitude in hippocampal slices. Our data suggest that amiodarone reduces Ca2+ influx through N- and P/Q-type Ca2+ channels, subsequently reducing the Ca2+-calmodulin/protein kinase A cascade to inhibit the evoked glutamate release from rat hippocampal nerve terminals.